Emptiness is not so empty: The meaning of the Russian prefix вы- in the natural perfective verbs - Tatiana Pozolotina (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2009)
This paper analyzes the meaning of the so-called "empty" prefix вы- (‘out-') of natural perfective verbs in the Russian language. It is argued that the prefix is not semantically empty, but displays meanings that can be analyzed as a radial category.